Evaluation of Root Canal Obturation Bond Strength Following 2-Week Coronal Seal Loss and Thermal and Chewing Cycling: Ex Vivo Study - Abdulkarim M. Almousa; Smita D. Dutta; Saleh H. Alshudukhi; Nawaf M. Almutairi; Ahmed N. Mohamed (Journal of Pharmacy and Bioallied Sciences)
Objectives: This study aimed to evaluate the effect of two weeks of thermal and chewing cycling (T&C) on the adhesion of three endodontic sealers—AH Plus (AHP), EndoSequence BC (BC), and AH plus bioceramic (AHPBC)—using the push-out bond strength test. Materials and Methods: Eighty single-rooted mandibular premolars were selected, disinfected, and prepared using ProTaper Gold rotary files up to size F4. The samples were randomly divided into eight groups based on obturation technique and sealer type. The sealer types AHP, BC, and AHPBC were used with either the single cone or the continuous wave techniques. After obturation, the samples underwent thermal and chewing cycling (T and C) for 2 weeks consisting of 400 cycles of thermocycles (15°C–45°C) and 9,500 chewing cycles (30–50N). The parameters of push-out bond strength were measured, while the failure modes were evaluated under a stereomicroscope. Results: The obtained results from the push-out bond strength test showed significant differences between sealers and techniques of obturation. In the coronal third, bond strength was the highest, while the middle and apical thirds followed. Continuous wave AHP with no T and C demonstrated the highest bond strength with 19.97 ± 10.54 MPa in the apical third. In contrast, AHPBC with T and C had the lowest bond strength in all sections. T and C had an unfavorable effect on the bond strength of AHP and AHPBC. However, T and C with BC showed improved adhesion. Conclusions: Thermal and chewing cycling (T and C) significantly influenced the adhesion of endodontic sealers. AHP and AHPBC demonstrated reduced bond strength after T and C, while BC showed improved performance. These findings suggest that long-term clinical success may be influenced by the choice of sealer and obturation technique in conditions simulating coronal seal loss.